PELATIHAN PEMBUATAN MEDIA BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KREATIVITAS PESERTA DIDIK SMP NEGERI 3 KABUH JOMBANG - Diah Dinaloni; Henky Muktiadji; Meriena Mustikaning Kussusilo (Yayasan Education and Social Center, 2026)
The basic challenge facing the world of education today is the widespread use of modern learning media that tends to be uniform and overlooks the characteristics of the surrounding environment. The impact is that students feel alienated from their own culture. In fact, learning will only be meaningful if it is contextual by connecting students to social reality and the potential of the area where they live. Therefore, incorporating elements of local wisdom into learning media and teaching materials not only makes it easier to understand the material, but is also effective in sparking students' imagination and curiosity in a deeper way. Based on interviews with partner teachers and observations in May 2026, the learning process at the school is still dominated by conventional approaches that rely on formal textbooks and monotonous static visual media. This happens in social studies lessons for 7th-grade students on the topic of sustainable development. As a result, students seem less enthusiastic and passive during social studies lessons when the topic of sustainable development is taught, because the material is often considered boring due to the scope of the subject being too broad, so students can only guess how sustainable development is implemented in Indonesia. Responding to the urgency and various issues mentioned above, it is necessary to conduct a 'Training on creating media based on local wisdom to enhance the creativity of 7th-grade students at SMP Negeri 3 Kabuh, Jombang'. The implementation method of this program uses a persuasive, participatory, and experimental approach, divided into three systematic stages: preparation, implementation (training), and evaluation, which is measured using a Student Creativity Observation Sheet instrument covering aspects of fluency of thinking, flexibility, and originality of ideas. The results of the activities showed that using media based on local wisdom effectively made the learning atmosphere more lively and contextual. The final assessment places the student groups in the Creative to Very Creative category, where students are able to come up with ideas for using environmentally friendly natural materials, independently vary weaving techniques, and produce unique character visualizations